EFFECT OF DIFFERENT RATES OF (CHEMICAL AND ORGANIC FERTILIZERS) ON FRUITS YIELD AND OIL CONTENT OF CORIANDER (Coriandrum sativm) - Mothafer A. Al-Mosuly (Mesopotamia Journal of Agriculture)
Cultivated fruits Coriander conducted in sheets (1 x2 square meters) of soil type (Silty Loam) using animal compost (sheep waste) levels (0, 1, 2, 3, 4 and 5 tons. ha-1) and other chemical transactions at levels equaled values (NPK)valaes at in the organic compost, named N0P0K0 ,N18P2K3 ,N36P4K6 ,N54P6K9 ,N72P8K12 and N90P10K15 kg. Ha-1 (urea "45% N" source of nitrogen and phosphate Super unilateral "9% P" source of phosphorous and potassium sulphate "43% K" source of potassium). Results were : 1-Treatment comparison (without organic or chemical fertilizer) The sum of fruits (658 kg. Ha-1) and the quantity of oil (5.42 liters. ha-1). 2-Treatment (2 tons. 1 hectare) of manure gave the highest sum of fruits reached (1348 kg. Ha-1) and the highest quantity of oil (13.48 liters. ha-1). 3-N72P8K12 excelled treatment of chemical fertilizer excelled equaled 4 tons. 1 ha of compost gave the sum of the fruits of the (1008 kg. Ha -1), whereas treatment N54P6K9 was equivalent to 3 tons. 1 ha of compost) oil hit (11.25 liters. ha-1).